Comparison Of The Effectiveness Of Daily Versus Weekly Oral Iron Supplementation In Preventing Anemia During Pregnancy - Sadaf, Maliha; Iqbal, Khansa; Ahmed, Saira; Sehar, Mehak; Waheed, Nabeela (Journal of Rawalpindi Medical College, 2023)
Introduction: Daily oral iron and folic acid intake is recommended as part of antenatal care but adherence to this regimen, due to gastrointestinal side effects, interrupted intake of iron. Weekly oral iron therapy has been introduced as an alternative to the daily iron regimen. Objective: To compare mean hemoglobin and hematocrit in non-anemic pregnant females receiving daily oral iron versus weekly iron supplements in third trimester of pregnancy. Material and Methods This randomized Controlled Trial study was carried out in department of obstetrics and gynecology of holy family hospital, Rawalpindi during 20th November 2019 to 20th May 2020. 70 pregnant females of 15 to 45 years, with singleton pregnancies, at gestational amenorrhea 14 to 22 weeks at the time of inclusion with hemoglobin level 11g/dl and above were included. They were randomly divided into two equal groups using SPSS, Group A (35) received daily oral iron and Group B, 35 received weekly oral iron. Results: There was no statistically significant difference could be detected between both groups as regards the hemoglobin level before starting iron supplementation and duration of supplementation and this can be attributed to proper randomization. Mean post treatment hemoglobin was 13.2±0.93 g/dl in group A and 12.9±0.95 g/dl in group B (0.118), mean change of hemoglobin was 1.07±0.34 g/dl in group A and 0.63±0.56 g/dl in group B (0.000), mean post treatment hematocrit was 35.857±0.87 % in group A and 32.857±0.91 % in group B (p 0.000), mean change of hematocrit was 2.942±0.59 % in group A and 1.000±0.00 % in group B (p 0.000). Conclusion: Weekly iron supplementation as a prophylaxis in non-anemic pregnant women is as good as daily supplementation as regards the hemoglobin level.